Generational Symbolic Violence Against Women in Cigarette Girl by Ratih Kumala - Selma Aurelia; Ephrilia Noor Fitriana (Jurnal Ragam Pengabdian, 2026)
This study discusses symbolic violence against women of the novel Cigarette Girl by (Kumala, 2017) in the context of generational patterns. According to (Bourdieu, 1977) symbolic violence is an implicit, unseen, and often hidden type of domination, which is based on cultural norms, social expectations, and the daily practices. The study employs the notions of symbolic violence, habitus, doxa, capital, and field as posited by Bourdieu to the research in order to understand how gendered domination is internalized and reproduced across generations within the family setups, practices in the industry, and cultural traditions as portrayed in the novel. The study reviews and identifies the instances of symbolic violence using qualitative textual analysis and close reading of narration, dialogue, and interaction of characters, based on silencing, emotional containment, lack of autonomy, and normalization of gender inequality. The results prove that symbolic violence towards women in Cigarette Girl is perpetuated across the generations based on the family values, the cultural memory, and patriarchal conventions institutionalized in the domestic and social sphere.